Cathodic stripping square-wave voltammetry for assessing As(III) removal with synthetic mixed oxides - Heredia, Angelica Constanza (2017)
The possibility of counting with a reliable and economic system for filtering large volumes of water contaminated with arsenic is highly desired since different species of this element conform a major health risk through contamination of drinking and irrigation water supplies. In this work, the adsorption of As(III) species from aqueous solutions onto Mixed Oxides (MOs) synthesized from Layered Double Hydroxides (LDHs) has been assessed by cathodic stripping Square-wave voltammetry (CS-SWV). This electrochemical technique provides the fast, reliable, and systematic analysis required for studding the numerous aqueous samples. The optimized protocol consisted on the accumulation of arsenic for 60 s at ?0.4 V, in presence of 0.5 mM Cu(II), 0.3 µM pyrrolidine dithiocarbamate (PDTC), and 0.9 M HCl, followed by a reductive scan to ?1.0 V. A stable and well-defined peak was observed at ?0.780 V, with a linear range that goes from 2 µg L?1 to 110 µg L?1 of As(III). A value of limit of detection (LOD) = 4 µgL?1 was calculated as 3 times the ratio between the standard deviation of the ordinate and slope of the linear regression curve. The presence of Cu(II) increases the signal of current and minimizes the effect of interfering species, while the ligand PDTC forms a complex that stabilizes the signal observed during the cathodic scan.A series of MgAlFe ternary LDHs with different iron content and their MOs have been synthesized by co-precipitation and characterized by diverse techniques. XPS and DRUV-Vis analysis showed that the Fe(III) ions can be found in tetrahedral and octahedral coordination environments, while SEM micrographs, evidenced the cluster formation and aggregates of particles when the Fe/(Fe+Al) molar ratio is increased. The capacity of MOs for removing As(III) has been studied at different contact times in a batch reactor and in all cases removals of As(III) above 75% were achieved.